Green Online Food Delivery In Tourist Destinations: Analysis of Tourists' Value on Attitude And Purchase Intentions - Prawira, Aura Bulan Andhara; Giovanni, Elvia; Prawira, Mega Fitriani Adiwarna; Nugraha, Siti Yulia Irani; Widyastuti, Sri Utari (Journal of Consumer Studies and Applied Marketing, 2024)
This study investigates the implementation of environmentally friendly online food delivery services in tourist destinations, aiming to align with the principles of sustainable tourism. The primary objective is to analyze how tourist values influence their attitudes and purchase intentions toward online food delivery in these destinations. A quantitative research method is employed, utilizing Structural Equation Modeling-Partial Least Squares (SEM-PLS) to assess the impact of customer value on attitudes and purchase intentions toward Green Online Food Delivery (Green OFD). The study sample comprises 120 tourists with prior experience using online food delivery services during their visits to tourist destinations. The results indicate that the availability of Green OFD, derived from environmentally friendly local products, significantly affects tourists' attitudes and purchase intentions, especially among those who are mindful of sustainability issues. Tourists demonstrate positive attitudes and purchase intentions when they recognize functional, emotional, social, and epistemic values, including the feeling of contributing to environmental conservation by opting for Green OFD. The findings offer theoretical and practical insights for advancing sustainable tourism destination development.